A case report of congenital bullous ichthyosiform erythroderma caused by a mutation of KRT10 gene - Yichuan GAN; Sanquan ZHANG; Xiaodong LI; Rujun XUE; Yidan FU; Biaoyi LUO; Wei LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To identify KRT1 and KRT10 gene mutation in a patient with bullous ichthyosiform erythroderma (BCIE). Methods Peripheral bloods of the patient and her families were collected and DNAs were extracted. All coding exons and flanking sequence of the KRT1 and KRT10 genes were amplified by PCR. PCR products were directly sequenced to detect mutations. Potential gene mutations were detected by Sanger sequencing method. Results A heterozygous missense mutation c. 467G>A in exon 1 of KRT10 gene was identified, which led to the protein at position 156 unnormal (p. Arg156His); The mutation was not found in the patient's father, mother and sister. Another heterozygous repeat mutation NM_000421.5: c. 1654_1683dups in exon 7 of KRT10 gene in the patient and her mother between 1654 and 1684 was identified, and these mutations result in glycine repeats (p. Gly556_Gly565dup) at positions 556 to 565, which was heterozygous. There was no mutation in other members of this family, so it was suggested that it was a new mutation. There was no mutation of KRT1 in all samples. Conclusion Mutation of c. 467G>A is the pathogenic cause of BCIE in this case and the mutation of 000421.5: c. 1654_1683dup of KRT10 gene may not be the pathogenic cause.